Ultrasensitive detection of L-phenylalanine on DC magnetron sputtered bismuth thin films using label-free SERS method - Risa Marium Philip; Bharathi Mohan D (Next Materials, 2024)
Quantitative imbalances in monomers such as amino acids, nucleotides etc. act as biomarkers for various health conditions like cancer, Alzheimer’s, genetic disorders etc. Different atmospheric annealed bismuth (Bi) thin films deposited by DC magnetron sputtering were compared to select a better Surface Enhanced Raman Spectroscopy (SERS) platform. The tailored morphology favoured confining of localized surface plasmon resonance (LSPR) between close-packed Bi nanoparticles. The Multiple SPRs (Mult. SPRs) from interband plasmonic transitions are majorly present in the ultraviolet (UV)-near-visible region making the film a promising UV- SERS platform. The varied annealing’s have tuned the SPR and are supported by the colour changes of Bi films. The Raman modes confirmed the chemical stability the films. XPS etching revealed the metallic state of the optimized Bi-D-PDV2 film. The preliminary SERS applications on Rhodamine 6 G (RH6G) selected a Bi-D-PDV2 film with an enhancement factor (EF) of ∼4 ×105. This optimized film used for L-phenylalanine (Phe) detection, resulted in enhanced sensitivity of ∼2 ×106 EF with a sub-micromolar (0.1 μM) limit of detection (LOD). The ultra-sensitive responses in the sub-μM level from the optimized Bi thin film for standard as well as biomolecule is reported for the first time to the best extent of knowledge. The potential responses from the optimized film gives promising response for its use in ultra-sensitive bio detections even down to single molecular level in future.